Bahasa Inggris Bahasa Inggris - Alifa Fajriani Martius; Emma Yuliani; Andre Primantyo Hendrawan; Very Dermawan (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates groundwater flow and nitrate transport in the Kasin Sub-watershed, Malang City, using Visual MODFLOW integrated with the MT3DMS module. Hydrogeological and geoelectrical data, groundwater levels, and nitrate concentration measurements (110 ppm) were used as model inputs. A transient simulation over 3,600 days (±10 years) was conducted to analyze plume migration. The results show that groundwater flow follows topographic gradients, moving from upland recharge zones to lowland discharge zones, with an average velocity of 0.25–0.40 m/day. The nitrate plume migrated southward, extending ±600–700 m horizontally and reaching ±25 m in depth. High concentrations (>100 ppm) remained near the source, while concentrations decreased to 20–40 ppm at greater distances due to advection and dispersion. Vertical sections indicated plume penetration into deeper aquifers, influenced by hydraulic pressure differences between strata, while permeable sandy and pumice tuff layers facilitated migration and clay acted as aquitards. These findings highlight the persistent nature of nitrate contamination, the role of aquifer heterogeneity, and the vulnerability of groundwater in urban catchments. In conclusion, nitrate pollution poses long-term risks to groundwater quality, emphasizing the importance of monitoring networks, aquifer protection policies, and improved land-use management to mitigate further contamination.